Biología reproductiva de Potamorhina altamazonica (Cope, 1879) "llambina" y Brycon amazonicus (Agassiz, 1829) "sábalo cola roja) en el bajo Amazonas, Caballococha, Loreto-Perú,2020 - Salazar Maco, Karina Mabel (2022)
The purpose of this thesis work was to determine the reproductive biology of Potamorhina altamazonica (cope,1879) “ llambina” and Brycon amazonicus ( spix y Agassiz,1829) “ red-tailed tarpon” in the lower Amazon, Caballo Cocha, Loreto – Perú, was carried out in the period from November 2020 to October 2021, using the methodology described by Tresierra, A., the specimens were obtained from the fishing landings port and the commercial market of the city of Caballo Cocha,as well as from exploratory fishing carried out in capture environments. 376 specimens of Potamorhina altamazonica and 250 of Brycon amazonicus were collected, the data of the reproductive aspects was made a ventral cut from the height of the operculum to the anal orifice of the fish then the biometric measurements were obtained using an ichthyometer and to obtain the weight of the fish and gonads a balance was used. In relation to Potamorhina altamazonica, its first sexual maturity for females is at 16 cm and for males at 17.6 cm of standard length. The sex ratio was 57.40% for females and 41 % for males, the gonadosomatic index the highest value of 30%, in January and in November the lowest value of 0.2% for females, in January the highest value of 17% and in November the lowest value of 0 % in males. in relation to Brycon amazonicus, its first sexual maturity of the females is at 29.5 cm and of the males at 27.9 cm of standard length. the sex ratio was 55.20% for females and 44.80% for males. the gonadosomatic index the highest value of 21% in April and in December the lowest value of 0 %for females, in January the highest value of 9 % and in December the lowest value of 0 % in males.